Long-term postural control in elite athletes following mild traumatic brain injury - Al-Husseini, Ali; Gard, Anna; Fransson, Per-Anders; Tegner, Yelverton; Magnusson, Måns; Marklund, Niklas; Tjernström, Fredrik (Frontiers in Neurology, 2022)
Background Traumas to the head and neck are common in sports and often affects otherwise healthy young individuals. Sports-related concussions (SRC), defined as a mild traumatic brain injury (mTBI), may inflict persistent neck and shoulder pain, and headache, but also more complex symptoms, such as imbalance, dizziness, and visual disturbances. These more complex symptoms are difficult to identify with standard health care diagnostic procedures. Objective To investigate postural control in a group of former elite athletes with persistent post-concussive symptoms (PPCS) at least 6 months after the incident. Method Postural control was examined using posturography during quiet stance and randomized balance perturbations with eyes open and eyes closed. Randomized balance perturbations were used to examine motor learning through sensorimotor adaptation. Force platform recordings were converted to reflect the energy used to maintain balance and spectrally categorized into total energy used, energy used for smooth corrective changes of posture (i.e., <0.1 Hz), and energy used for fast corrective movements to maintain balance (i.e., >0.1 Hz). Results The mTBI group included 20 (13 males, mean age 26.6 years) elite athletes with PPCS and the control group included 12 athletes (9 males, mean age 26.4 years) with no history of SRC. The mTBI group used significantly more energy during balance perturbations than controls: +143% total energy, p = 0.004; +122% low frequency energy, p = 0.007; and +162% high frequency energy, p = 0.004. The mTBI subjects also adapted less to the balance perturbations than controls in total (18% mTBI vs. 37% controls, p = 0.042), low frequency (24% mTBI vs. 42% controls, p = 0.046), and high frequency (6% mTBI vs. 28% controls, p = 0.040). The mTBI subjects used significantly more energy during quiet stance than controls: +128% total energy, p = 0.034; +136% low-frequency energy, p = 0.048; and +109% high-frequency energy, p = 0.015. Conclusion Athletes with previous mTBI and PPCS used more energy to stand compared to controls during balance perturbations and quiet stance and had diminished sensorimotor adaptation. Sports-related concussions are able to affect postural control and motor learning.